PENGARUH AKUNTABILITAS, TRANSPARANSI DA PENGAWASAN TERHADAP KINERJA ANGGARAN BERBASIS VALUE FOR MONEY (Studi Empiris pada Pemerimtah Kota Jayapura) - Cindy Arifani; Agustinus Salle; Andika Rante (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2018)
This study aims to analyze the effect of accountability, transparency, and supervision on the performance of budget based on the value for money. This research was conducted on 28 government agencies in Jayapura City. While, data collection in this research is usingquestionnaire, and sampling method that was used is purposive sampling with sample criteria that is Head of Department, Head of Finance, and Treasurer of each OPD exist in Jayapura Regency.The number ofsamples in this study approximately 100 people. The results show that accountability does not affect the performance of budget based on value for money, this means that the higher thelevel of accountability, the budget performance will be higher. Meanwhile, transparency affects budget performance: a value for money approach, this means the higher the level of transparency,the higher the budget performance. Supervision affects the performance of budget based on value for money. This means that with increasing oversight, budget performance will be increase as well